Analisis Dewan Syari'ah Nasional Tentang Akad Pembiayaan MurābaḤah Di Bmt Sakinah Bekonang Sukoharjo Tahun 2015 - Tayono, Tayono; , Drs. Harun, MH.; , Nurul Huda, M. Ag (2016)
Baitul Māl Wat Tamwil (BMT) is a financial institution which helps micro businesspeople and small businesspeople based on Sharia. In BMT, there is a program of financing such as the financing of murābaḥah. Along with the great quantities of murābaḥah system in the BMT institution, there are also great quantities of variation in implementing the financing system of murābaḥah, therefore, the writer is interested in studying "The Analysis of The National Sharia Board on The Implementation of Murābaḥah Agreement in BMT Sakinah Bekonang Sukoharjo". The problem statements are: How is the implementation of murābaḥah agreement in BMT Sakinah Bekonang Sukoharjo and how is the view of the National Sharia Board on the financing of murābaḥah agreement? Meanwhile, the objectives of this research are to know the implementation of murābaḥah agreement in BMT Sakinah Bekonang Sukoharjo and to know how the analysis of the National Sharia Board on the implementation of murābaḥah agreement. This research used the type of qualitative research. The sources of data were obtained from the primary data (directly) which were from the field research through, interview with the manager as the person in charge of BMT Sakinah, and the secondary data (indirectly) which were from other literatures being relevant to the studied problems. Besides interview, the methods of data collection which were used were observation and documentation. Meanwhile, the method of data analysis was a descriptive analysis aiming at describing the phenomenon or the real condition in the implementation of murābaḥah agreement in BMT Sakinah Bekonang Sukoharjo. From the result of the research, it was known that the murābaḥah agreement in BMT Sakinah had been appropriate to Sharia because of fulfilling the requirements and the essential pillars. Besides, in the implementation, the customers conducted installment for a period of time determined by BMT Sakinah without breaking the Sharia laws because there had been an agreement and signing early when the customer and the side of BMT Sakinah agreed each other. The implementation of murābaḥah agreement in BMT Sakinah Bekonang Sukoharjo refered to The National Sharia Board in their decree 04/DSN-MUI/VI/2000 that is in the first section: The General Stipulations of Murābaḥah in the Sharia Bank Number 5 and 7 which explain: (No. 5) Bank must conveys everything related to the buying, for example if the buying is conducted through credit and (No. 7) The customer pays the price of items which has been agreed in a certain period of time which has also been agreed.